Mtoro bin Mwinyi Bakari : Swahili lecturer and author in Germany - Wimmelbücker, Ludger (Book collections on Project MUSE., 2009)
This book presents a study of the life history of Mtoro bin Mwinyi Bakari (c. 1869- 927). Mtoro bin Mwinyi Bakari grew up and studied Islamic Sciences in Bagamoyo, Tanzania. He became a Swahili lecturer and author in Germany and is known to have written Desturi za Wasuaheli, an important work in Swahili culture. The book introduces the wider historical context of his writings, and, in particular, reconstructs the racism and discrimination in both the colonial and metropolitan contexts, features which negatively influenced his career and his life as a whole. The study also offers insights into contributions of the colonized to the study of African languages and cultures during this same historical context.